The Medicaid Expansion and Attitudes toward the Affordable Care Act: Testing for a Policy Feedback on Mass Opinion. Issue 1 (6th April 2019) - Hopkins, Daniel J; Parish, Kalind
Abstract: Enacted in 2010, the Affordable Care Act (ACA) has reshaped US health policy. Yet overall opinions on the law remained relatively stable during the few years before and after enactment. In a polarized era, can the implementation of a complex program such as the ACA influence public opinion through a policy feedback? Research on policy feedbacks and self-interest provide competing expectations. To address that question, we consider the impact of the Medicaid expansion that took place in select states. Using differences-in-differences estimation and 2010–2017 surveys of more than 51, 000 non-elderly American adults, we show that the Medicaid expansion made low-income Americans on average 4.4 percentage points more favorable toward the ACA (SD = 1.7) relative to those in non-expansion states. Given that no such effect emerged for high-income respondents, these results are consistent with an impact via self-interest and with a policy feedback on public opinion.